Assertive Behavior in Classical Counseling Guidance Services to Improve Adolescent Social Skills - Umar Diharja; Rini Sugiarti; Erwin Erlangga (Psikostudia : Jurnal Psikologi, 2025)
This project aims to investigate how intervention methods might be tailored to meet the individual requirements of teenagers from diverse cultural and social backgrounds. The objective is to make substantial contributions to education and developmental psychology, particularly in enhancing adolescent social skills via the implementation of assertive conduct in traditional counseling guidance services. The descriptive qualitative research method employing a case study methodology seeks to deliver a comprehensive grasp of the occurrences encountered by the research subjects. Site of investigation This study was performed on students at SMPIT Mutiara Cendekia Lubuklinggau, situated on Jalan Jenderal Sudirman, Jogoboyo Village, Lubuklinggau Utara II District, Lubuklinggau City. The study's findings indicated that assertive behavior is a crucial component in fostering successful communication and cultivating healthy social ties among students. In classical counseling guidance services, students are instructed to excel in several facets of assertiveness, including making requests, issuing refusals, self-expression, offering praise, and participating in conversations. The cultivation of assertive skills via traditional counseling services substantially enhances students' psychological well-being, communication abilities, and social interactions. Students enjoy enhanced self-confidence and can make substantial contributions to the improvement of social skills within the educational environment. Proficiency in social skills, encompassing empathy, cooperation, verbal and non-verbal communication, together with the capacity for constructive conflict resolution, fosters an inclusive and collaborative social environment that enhances collective learning. Penelitian ini dilatarbelakangi menggali secara mendalam bagaimana model intervensi dapat disesuaikan kebutuhan spesifik remaja dengan berbagai budaya dan sosial. Tujuan memberikan kontribusi signifikan bagi bidang pendidikan dan psikologi perkembangan, khususnya dalam upaya meningkatkan keterampilan sosial remaja melalui penerapan perilaku asertif dalam layanan bimbingan konseling klasikal. Metode Penelitian kualitatif deskriptif yang menggunakan pendekatan studi kasus bertujuan untuk memberikan pemahaman mendalam mengenai fenomena yang dialami oleh subjek penelitian. Lokasi penelitian Penelitian ini dilaksanakan pada siswa SMPIT Mutiara Cendekia Lubuklinggau yang beralamatkan di Jalan Jenderal Sudirman Kelurahan Jogoboyo Kecamatan Lubuklinggau Utara II Kota Lubuklinggau. Hasil penelitian didapatkan bahwa perilaku asertif merupakan elemen penting dalam pengembangan komunikasi efektif dan hubungan sosial yang sehat di kalangan siswa. Layanan bimbingan konseling klasikal, siswa dilatih untuk menguasai berbagai aspek asertivitas, yaitu permintaan, penolakan, pengekspresian diri, pujian, dan berperan dalam pembicaraan. Pengembangan keterampilan asertif melalui layanan bimbingan konseling klasikal memberikan dampak positif yang signifikan terhadap kesejahteraan psikologis, keterampilan komunikasi, dan hubungan sosial siswa. Siswa tidak hanya mengalami peningkatan dalam aspek kepercayaan diri sebagai individu, tetapi juga mampu memberikan kontribusi yang signifikan dan bermakna dalam meningkatkan keterampilan sosial di lingkungan sekolah. Penguasaan keterampilan sosial dengan empati, kerjasama, komunikasi verbal dan non-verbal, serta kemampuan untuk menyelesaikan konflik secara konstruktif dapat menciptakan lingkungan social yang inklusif, kolaboratif, dan mendukung proses pembelajaran bersama.